2023
DOI: 10.1007/s40123-023-00675-3
|View full text |Cite
|
Sign up to set email alerts
|

Blue Light Exposure: Ocular Hazards and Prevention—A Narrative Review

Abstract: Introduction Exposure to blue light has seriously increased in our environment since the arrival of light emitting diodes (LEDs) and, in recent years, the proliferation of digital devices rich in blue light. This raises some questions about its potential deleterious effects on eye health. The aim of this narrative review is to provide an update on the ocular effects of blue light and to discuss the efficiency of methods of protection and prevention against potential blue light-induced ocular injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
27
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 175 publications
4
27
0
3
Order By: Relevance
“…Ocular phototoxicity involves damage caused by exposure to light, particularly short-wavelength blue light, leading to harmful reactions in ocular tissues. Although ordinary ambient sunlight exposure does not cause phototoxicity, the concern is that prolonged or intense blue light exposure could contribute to ocular phototoxicity [32,35] . Short-wavelength blue light easily penetrates through the lens to reach the RPE cells, and then interacts with accumulated lipofuscin, as well as photosensitizers such as flavin and porphyrins within abundant mitochondria in retina cells [5,12] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ocular phototoxicity involves damage caused by exposure to light, particularly short-wavelength blue light, leading to harmful reactions in ocular tissues. Although ordinary ambient sunlight exposure does not cause phototoxicity, the concern is that prolonged or intense blue light exposure could contribute to ocular phototoxicity [32,35] . Short-wavelength blue light easily penetrates through the lens to reach the RPE cells, and then interacts with accumulated lipofuscin, as well as photosensitizers such as flavin and porphyrins within abundant mitochondria in retina cells [5,12] .…”
Section: Discussionmentioning
confidence: 99%
“…Blue light and its potential connection to ocular phototoxicity have been subjects of scientific investigation [4,[32][33][34] . Ocular phototoxicity involves damage caused by exposure to light, particularly short-wavelength blue light, leading to harmful reactions in ocular tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Even though dentists and attending staff are unaffected by indirect viewing of light, eye protection is important. Concerns are developing that the population is exposed to increased blue light from multiple sources [25]. The widespread usage of blue light-emitting sources concerns all ages [25].…”
Section: Discussionmentioning
confidence: 99%
“…20 Young children are especially susceptible to their visual environment 21 and more sensitive to the blue light spectrum than adults due to their clear crystalline lens. 22 Exposure to blue-rich white light from screens and digital devices in the evening and at night disrupts sleep and natural ocular diurnal cycles, potentially impacting choroidal thickness and axial growth. For instance, Burfield et al 23 identified diurnal variations in ocular parameters such as choroidal thickness, axial length, intraocular pressure and ocular perfusion pressure.…”
mentioning
confidence: 99%
“…Rapid urbanisation and related lifestyle changes have long been linked to a significant increase in myopia globally 20 . Young children are especially susceptible to their visual environment 21 and more sensitive to the blue light spectrum than adults due to their clear crystalline lens 22 . Exposure to blue‐rich white light from screens and digital devices in the evening and at night disrupts sleep and natural ocular diurnal cycles, potentially impacting choroidal thickness and axial growth.…”
mentioning
confidence: 99%